A Study of e-Learning, Blended learning, and Traditional Teaching Methods to Motivate Autonomous Learning in English Reading Comprehension of Thais Learners - Pornpimon Saeheng (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
The purposes of this study were to examine the differences in learners’ satisfaction of using e-Learning, blended learning, and traditional teaching methods for TR and HI students and to study learners’ autonomy after receiving three different kinds of teaching methods. The informants were 90, second year students majoring in Tourism and Hospitality Industry which were divided by purposive sampling method into three groups of 30 learners, Group A received e-Learning method, Group B received Blended Learning method, and Group C received Traditional teaching style. The research instruments used for data collection were lesson plans, e-Learning program, learners’ perception questionnaires, interview questions, and English Reading Comprehension test (Pretest and Posttest). Quantitative data were collected and analyzed by mean, standard deviation. The interview data was read, reread, and then coded. Coding organized the raw data into meaningful categories. The results of this study indicated that the overall of students’ satisfaction and autonomous learning rate after receiving their teaching delivery methods were at “good.” Additionally, the interview results showed that the students were positively satisfied with e-Learning and blended learning. The students have become autonomous learning. Recommendations were made and presented in two categories: benefits of future practice and further research.